Assessing the Impact of Training on Knowledge Level of Dairy Farmers of Punjab during Transitional Period - Thakur, Niharika; Singh, Parminder; Kasrija, Rajesh; Kansal, S. K. (International Journal of Bio-resource and Stress Management, 2019)
The study was undertaken to assess the impact of training on knowledge level of dairy farmers of Punjab regarding incidence of various transitional diseases and on management, breeding and feeding practices during transitional period. A structured interview schedule was made for interviewing 250 dairy farmers of Punjab, India. Among the transitional diseases incidence of anoestrous, mastitis, retained placenta, repeat breeding, metritis, milk fever, dystokia and ketosis were 59.6%, 52%, 38%, 30%, 22.4%, 18%, 14.8% and 10.4% respectively. Special dry feed feeding, special mineral mixture feeding and conception rate at dairy farm was found to be significantly associated (p<0.01) with training. Particular diseases like metritis and repeat breeding were significantly associated (p<0.05) with training. However, parameters like dry period, normal calving, heats missed after calving were found to be non-significantly different between farmers who has taken training and not. But, the awareness perceived by the farmers after training in relation to feeding, breeding, management and health status was significantly higher during transitional period as compared to the farmers who did not undertake any training. So, proper coverage of topic on management of dairy animals during transitional period is must for making a training programme effective. Also, still more awareness and extension activities on transitional period management are the need of hour. The extension machinery should be constructed in such a way that it provides a bridge between scientists/researchers and dairy farmers for successful implementing the training programme for transitional period.